The Role of Counselor Ethics and Competence in Multicultural Counseling: Principles and Challenges - Muhammad Andi Setiawan; Indah Lestari; Maria Grace B. Mababa (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: Multicultural counseling plays a vital role in guidance and counseling, particularly in Indonesia, which is characterized by extensive cultural, ethnic, religious, and linguistic diversity. Objective: This study aims to examine the roles of counsellor ethics and multicultural competence in the implementation of multicultural counseling and to identify the challenges encountered in practice. Method: The study employs a qualitative literature review design, analyzing relevant academic journals, books, and scientific publications on counsellor ethics, counsellor competence, and multicultural counseling. Result: The findings indicate that professional ethics serve as a fundamental guideline for counsellors in respecting clients’ rights, dignity, and cultural values, while multicultural competence enables counsellors to understand cultural differences, manage personal biases, and apply appropriate counseling strategies. The integration of ethical principles and multicultural competence contributes significantly to the delivery of inclusive, effective, and equitable counseling services. Conclusion: The study emphasizes that strengthening ethical awareness and multicultural competence is essential for enhancing the quality and professionalism of counseling services in multicultural contexts. Contribution: This study provides a conceptual synthesis that underscores the interdependence between ethical standards and multicultural competence as a framework for advancing culturally responsive counseling services.